2022
DOI: 10.1001/jamanetworkopen.2022.44679
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Problematic Alcohol Use Among Physicians: A Systematic Review

Abstract: ImportanceProblematic alcohol use in physicians poses a serious concern to physicians' health and their ability to provide care. Understanding the extent and characteristics of physicians with problematic alcohol use will help inform interventions.ObjectiveTo estimate the extent of problematic alcohol use in physicians and how it differs by physician sex, age, medical specialty, and career stage (eg, residency vs practicing physician).Evidence ReviewPreferred Reporting Items for Systematic Reviews and Meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
(220 reference statements)
0
8
0
Order By: Relevance
“…Alcohol and substance misuse are not uncommon in the healthcare professions. A systematic review of 31 studies involving 51,680 participants in 17 countries, problematic alcohol use was reported by physicians and increased over time (from 16.3% in 2006–2010 to 26.8% in 2017–2020) [ 56 ]. A survey of ED doctors found that (despite being trained in the detection of alcohol misuse) 63% reported that they misuse alcohol at least once a month and 30% once or more a week [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and substance misuse are not uncommon in the healthcare professions. A systematic review of 31 studies involving 51,680 participants in 17 countries, problematic alcohol use was reported by physicians and increased over time (from 16.3% in 2006–2010 to 26.8% in 2017–2020) [ 56 ]. A survey of ED doctors found that (despite being trained in the detection of alcohol misuse) 63% reported that they misuse alcohol at least once a month and 30% once or more a week [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increase in alcohol-related deaths in the US over the last 2 decades, little is known about alcohol-related mortality risks among physicians and other health care workers. Compared with non–health care workers, health care workers have increased drug overdose death risks . An occupational liability to substance use or to risks of painful injuries and access to controlled substances may explain these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non–health care workers, health care workers have increased drug overdose death risks. 4 An occupational liability to substance use or to risks of painful injuries and access to controlled substances may explain these findings. Only the first hypothesis would contribute to an increased risk of alcohol-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests a high prevalence of alcohol misuse among physicians, specifically surgeons [ [1] , [2] , [3] , [4] ]. Furthermore, there are grounds to assume that global alcohol consumption among healthcare workers has increased since the onset of the COVID-19 pandemic [ [5] , [6] , [7] , [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%